An In Vitro Comparison of Marginal Adaptation of MTA and MTA-Like Materials in the Presence of PBS at One-Week and Two-Month Intervals. - Abdollah Ghorbanzadeh; Noushin Shokouhinejad; Bita Fathi; Maryam Raoof; Mehrfam Khoshkhounejad (Tehran University of Medical Sciences, 2014)
This study compared the marginal adaptation of mineral trioxide aggregate (MTA) and MTA-like materials as root-end fillings after incubation in phosphate buffer saline (PBS), a synthetic tissue fluid, for either 1 week or 2 months.In this experimental study, seventy-two extracted human single-rooted teeth were prepared and obturated with gutta-percha and AH26 sealer. The apical 3 mm of the roots were resected. Root-end cavities were prepared with an ultrasonic retrotip. The specimens were randomly divided into three groups (n=24) and filled with either ProRoot MTA, OrthoMTA, or RetroMTA. Half of the specimens in each group were stored in PBS for 1 week the other half for 2 months. Epoxy resin replicas from the resected root-end surfaces and longitudinally sectioned roots were fabricated. The gaps at the material/dentin interface were measured using a scanning electron microscope (SEM). Transversal, longitudinal, and overall gap sizes were measured. The data were analyzed using Kruskal-Wallis and Mann-Whitney tests. The significance level was set at p < 0.05.There were no significant differences between the marginal adaptation of ProRoot MTA, RetroMTA, and OrthoMTA in both transverse and longitudinal sections after incubation for either 1 week or 2 months (p > 0.05). In addition, the test groups were not significantly different regarding the overall mean gap values (p > 0.05).Under the conditions of this study, there was no difference between the marginal adaptation of ProRoot MTA, OrthoMTA, and RetroMTA as root-end filling materials after exposure to PBS for either 1 week or 2 months.